1989
DOI: 10.1257/jep.3.3.129
|View full text |Cite
|
Sign up to set email alerts
|

Cash Distributions to Shareholders

Abstract: Economists have long been puzzled by why firms pay dividends when alternative methods of rewarding shareholders and financiers exist which involve less taxes. This paper will highlight the fact that firms can distribute cash to equity holders in ways more lightly taxed than dividends. The two methods we examine are share repurchase programs and cash-financed mergers and acquisitions. So why should cash distributions from firms to shareholders ever take the form of dividends? This paper first provides evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
113
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(122 citation statements)
references
References 16 publications
(12 reference statements)
7
113
1
Order By: Relevance
“…While there seems to be a historical trend from dividends to repurchases (Bagwell and Shoven [19], Fama and French [20], Grullon and Michaely [21]), (Allen and Michaely [7] p. 421) report that dividends and repurchases payouts when combined had remained fairly constant in the previous ten years. Lee and Suh [22] found that repurchases are often accompanied by increases in dividend payout.…”
Section: Dividends and Repurchases As Payout Optionsmentioning
confidence: 99%
“…While there seems to be a historical trend from dividends to repurchases (Bagwell and Shoven [19], Fama and French [20], Grullon and Michaely [21]), (Allen and Michaely [7] p. 421) report that dividends and repurchases payouts when combined had remained fairly constant in the previous ten years. Lee and Suh [22] found that repurchases are often accompanied by increases in dividend payout.…”
Section: Dividends and Repurchases As Payout Optionsmentioning
confidence: 99%
“…Within this context, the personal tax savings hypothesis, states that share repurchases can be more tax efficient and more beneficial to shareholders, compared to cash dividends (Grullon and Michaely 2002). While Bagwell and Shoven (1989) and Dittmar (2000) find no evidence of taxation having a significant impact on corporate payouts, a number of research studies do find evidence of tax having a significant influence on firms' decision making on payouts, and of the market having a favorable reaction due to the tax impact (Masulis 1980;Grullon and Michaely 2002). Furthermore, open market share repurchases can have advantages relative to cash dividends such as tax differential and that they do not pose a commitment to the firm.…”
Section: Datamentioning
confidence: 99%
“…Further, the papers analyzed the tax effects on payout policy are Black (1976), Miller (1977), Miller and Scholes (1978), Peterson et al (1985), Hubbard and Michaely (1997), Allen et al (2000), Christoffersen et al (2005), and Desai and Jin (2011). Moreover, the studies investigated the stock repurchases are Dann (1981), Bagwell and Shoven (1989), Skinner (2008), and von Eije and Megginson (2008). Furthermore, the literature analyzed the payout policy from the viewpoints of behavioral economics and behavioral finance are Shefrin and Statman (1984), Stein (1989Stein ( , 1996, Wurgler (2004a, 2004b), and Graham and Kumar (2006).…”
Section: Introductionmentioning
confidence: 99%